TEACHING WRITING AND READING FOR YOUNG LEARNERS - Xolmatova Hamrobi Shermurod qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article outlines key strategies for teaching writing and reading to young learners, focusing on literacy’s role in academic success, communication, and critical thinking. It covers phonics-based instruction, guided and interactive writing, phonemic awareness, and vocabulary development. The article also addresses challenges like varying student abilities and offers solutions through differentiated teaching. Tailored strategies help educators create supportive learning environments for literacy and reading comprehension development.